Gelation of solvent-free electrolyte using siliceous materials with different size and porosity for applications in dye sensitized solar cells. (February 2016) - Vittoni, Chiara; Sacchetto, Vittoria; Costenaro, Daniele; Mastroianni, Simone; Hinsch, Andreas; Marchese, Leonardo; Bisio, Chiara
Highlights: Silica particles with different structure and textural properties were used as gelling agents of liquid electrolytes in DSSC. The addition of water-in-oil silica particles allowed an increase up to 14% of the overall solar cell efficiency. Phenomena occurring when quasi-solid gel electrolytes are used for DSSC preparation were carefully investigated. Abstract: In this study, silica samples with different structure and particle size were used as additives for the stabilization of liquid electrolytes in Dye Sensitized Solar Cells (DSSCs) in order to assess the influence on the final performances of the devices. In particular, three different silica-based materials were synthetized: monodispersed silica particles with different size (prepared by Stöber and water-in-oil microemulsion methods) and porous ordered mesostructured silica (MCM-41). In addition, organo-silica materials containing basic NH2 species were also prepared. It was observed that the introduction of silica additives has positive effects in terms of devices efficiency. In particular, the electrolyte containing monodispersed silica particles with smallest dimensions showed an increase up to 14% of the overall efficiency. A detailed electrochemical characterization was carried out in order to have a deeper understanding on phenomena occurring when quasi-solid electrolytes are used for DSSC preparation.